Chef Lenny Widjaja’s Introducing Baking Learning Content with Instagram Social Media - Hartman, Gabrille; Meisyaroh, Siti (Jurnal Komunikasi dan Bisnis, 2024)
A chef's shift to social media often comes in response to changing consumer behavior trends. One individual who has been successful in utilizing social media to introduce cooking learning content is Chef Lenny Widjaja. Therefore, the aim of this research is to analyze what creative strategies are applied in introducing baking learning content via social media Instagram (@cheflennywidjajaofficial). This research is based on the concept of creative strategy, namely creative brief. The subject of this research is Chef Lenny Widjaja's baking learning content with the research design used a qualitative descriptive approach. Data collection techniques use semi-structured interviews and documentation. The research results obtained are all information related to the creative brief that was prepared to create baking learning content. The creative brief also explains all the elements included in the creative brief such as the purpose of creating baking learning content, the target audience for the baking learning content, the message and tone included in the caption of the content that has been uploaded, research results on the latest food trends, setting boundaries such as time constraints, measuring success or metrics. Based on this research, it can be concluded that Chef Lenny Widjaja's creative strategy in introducing baking learning content through the social media Instagram is in accordance with the concept of creative strategy, namely the use of all creative brief elements in all content creation so that the content presented remains interesting, the number of viewers is stable and many course participants. creation so that the content presented remains interesting, the number of viewers is stable and many course participants.